1993
DOI: 10.1016/0270-9139(93)90112-z
|View full text |Cite
|
Sign up to set email alerts
|

A macroregenerative nodule containing multiple foci of hepatocellular carcinoma in a noncirrhotic liver

Abstract: We report an incidental small hepatocellular carcinoma in a patient with chronic hepatitis C infection without cirrhosis. The existence of portal triads and the Meyenburg complexes within the lesion and atypical subnodules suggests that the carcinoma has arisen in the context of a macroregenerative nodule rather than the whole nodule being an early, spreading carcinoma. A growing body of evidence supports macroregenerative nodules as being precursor lesions in the development of hepatocellular carcinoma. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…After evaluation of entire cases, 1–2 representative tumor blocks/case were chosen that showed the least amount of necrosis and/or hemorrhage, and that included background liver for immunohistochemistry. Tumor classification was based on 2010 World Health Organization, 19 and combined hepatocellular carcinoma -cholangiocarcinoma cases were excluded from the study. Fibrosis staging (0–4) was determined using Scheuer criteria 20 .…”
Section: Methodsmentioning
confidence: 99%
“…After evaluation of entire cases, 1–2 representative tumor blocks/case were chosen that showed the least amount of necrosis and/or hemorrhage, and that included background liver for immunohistochemistry. Tumor classification was based on 2010 World Health Organization, 19 and combined hepatocellular carcinoma -cholangiocarcinoma cases were excluded from the study. Fibrosis staging (0–4) was determined using Scheuer criteria 20 .…”
Section: Methodsmentioning
confidence: 99%
“…11 The HCCs were graded as per the WHO grading system into well differentiated, moderately differentiated, or poorly differentiated. 2 …”
Section: Case Selection and Histologic Reviewmentioning
confidence: 97%
“…1 In the 2010 World Health Organization (WHO) classification, hepatic adenomas are classified into 4 subtypes: hepatocyte nuclear factor 1 alpha (HNF1a) inactivated, inflammatory, b-catenin activated, and unclassified. 2 The WHO hepatic adenoma classification is achieved in most cases by using an immunostain panel composed of liver fatty acid-binding protein (LFABP), serum amyloid A (SAA) protein, C-reactive protein (CRP), b-catenin, and glutamine synthetase (GS). The loss of LFABP is characteristic of the HNF1a-inactivated subtype, whereas the expression of SAA protein and/or CRP defines the inflammatory subtype.…”
mentioning
confidence: 99%
“…10). A minor degree (stage) of fibrosis in areas devoid of iron could be a direct consequence of iron loss (less toxicity) and/or related to the malignant process [16,17] in its early phase (as denoted by absence of cellular disorganization, and negativity of the MIB-1 immunostaining). It was concluded that this patient needs a strict surveillance because he may be at risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%